2021
DOI: 10.3390/nu13020536
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Mocha Coffee Consumption Is Associated with Higher Cognitive and Mood Status in a Non-Demented Elderly Population with Subcortical Ischemic Vascular Disease

Abstract: To date, interest in the role of coffee intake in the occurrence and course of age-related neurological and neuropsychiatric disorders has provided an inconclusive effect. Moreover, no study has evaluated mocha coffee consumption in subjects with mild vascular cognitive impairment and late-onset depression. We assessed the association between different quantities of mocha coffee intake over the last year and cognitive and mood performance in a homogeneous sample of 300 non-demented elderly Italian subjects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 89 publications
(111 reference statements)
0
14
0
1
Order By: Relevance
“…Researchers discovered a significant difference in age and education among the four groups of subjects based on their daily mocha coffee consumption. However, the General Regression Model revealed that the associations between coffee consumption and cognition and mood were independent of socio-demographic variables ( Fisicaro et al, 2021 ). In terms of the sex-related effect, an earlier prospective study ( Shinoda et al, 2015 ) of 455 participants (314 men) found that male drinkers had a lower incidence of small vessel disease than male non-drinkers and occasional drinkers, while female drinkers had a lower incidence of white matter lesions (WMLs) than female non-drinkers or occasional drinkers.…”
Section: Sex-specific Differences In Vadmentioning
confidence: 99%
“…Researchers discovered a significant difference in age and education among the four groups of subjects based on their daily mocha coffee consumption. However, the General Regression Model revealed that the associations between coffee consumption and cognition and mood were independent of socio-demographic variables ( Fisicaro et al, 2021 ). In terms of the sex-related effect, an earlier prospective study ( Shinoda et al, 2015 ) of 455 participants (314 men) found that male drinkers had a lower incidence of small vessel disease than male non-drinkers and occasional drinkers, while female drinkers had a lower incidence of white matter lesions (WMLs) than female non-drinkers or occasional drinkers.…”
Section: Sex-specific Differences In Vadmentioning
confidence: 99%
“…Fourthly, the lack of a group of patients with H-type hypertension but no SIVD prevented a deeper analysis of the effects of gender differences. Finally, in addition to the risk factor for SIVD and the role of H-type hypertension, future study may also consider the effect of protective factors in this population, such as the role of caffeine or acetyl-L-carnitine intake on mood and cognition ( Pennisi et al, 2020 ; Fisicaro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, interventions that slow the hallmarks of aging will decrease the risk of both groups of diseases. It has been consistently shown that a healthy lifestyle and metabolism can decrease the risk of both cancer and cognitive decline [ 61 , 62 , 63 , 64 , 65 , 66 ]. In addition, related interventions are known to decrease markers of inflammation, improve mitochondrial health and decrease oxidative stress [ 67 , 68 ].…”
Section: Introductionmentioning
confidence: 99%